THE CONTROVERSY OF ANNE BOLEYN CHARACTER AS POTRAYED IN THE OTHER BOLEYN GIRL MOVIE - SEPTIARISA, AMELIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: controvesy, feminism, The Other Boleyn Girl. Feminism tells about women movement. Women believe that they have same value with men, they can do the same like men. They prove that they can make their own life better without following men’s instruction. Some women also show that they can reach her dream even some people said that is impossible. This phenomenon shows in a movie The Other Boleyn Girl which tells about an ordinary woman named Anne Boleyn who has an ambition to become the queen of England and she reaches her dream use controversial way. Thus, the aim of this research is to find out the controversy portrayed in Anne Boleyn character in the movie.The writer watches the movie so many times and then analyzes women character in Henry Tudor era, then the result will be use to discover Anne Boleyn’s controversy. Here, the writer also uses mise-en-scene to help gives more illustration related to the struggles that portraits in Anne Boleyn. Mise-en-scene help give more impression from setting, costume, lighting or the expression of the actors and actresses.This study reveals that woman struggle starts from feeling underestimated and controlled by others, especially men. However the movie The Other Boleyn Girl, shows that women in Henry Tudor era cannot make a movement or shows a struggle to change their fate. The action of Anne Boleyn character creates controversy at that time. Anne Boleyn’s struggles to shows the others that she as a woman can do something, woman can make everything possible. Anne Boleyn’s controversial act also broke assumption that woman is a weak person and was born to be men’sfollower.The writer suggests the next writers who want to analyze The Other Boleyn Girl movie to find out another special thing in the movie. If the next writer still wants to analyze the movie using feminism, maybe the next writer can choose another approach in feminism like woman subordination or patriarchy. If the next writers do not want to use feminism in their research they can use another approach like historical approach, because this movie adapted from England’s history.